Social Capital Theory, Social Exchange Theory, Social Cognitive Theory, Financial Literacy, and the Role of Knowledge Sharing as a Moderator in Enhancing Financial Well-Being: From Bibliometric Analysis to a Conceptual Framework Model - Thomas, Asha; Gupta, Vikas (Frontiers in Psychology, 2021)
A person's financial well-being (FWB) is the complete contentment gained from one's present finance condition. This has a powerful impact on the entire achievement of employee's "well-being". Researchers, financial analysts, financial planners, educationists, and economists have explored the "enablers" to improve employees' living standards by investigating the possible "financial well-being" resources for decades. There are a small number of researches conducted on FWB. There is no literature available to show the connection between social capital theory, social exchange theory, social cognitive theory, financial literacy and financial well-being, and employees' financial sharing of knowledge—a moderator to expand the complete financial well-being.